Inhibitory action of rice husk extract (RHE) on the corrosion of carbon steel in acidic media - O Olawale; A A Adediran; T Oyinbo; O Kalawole (Aceh International Journal of Science and Technology, 2017)
The study investigates the inhibition characteristics of rice husk extract (RHE) on the corrosion of mild steel in 1M acidic media. Mass loss, Fourier Transform Infrared Spectroscopy (FTIR), phytochemical analysis were used as basis for studying the corrosion inhibition behaviour of the extracts. The analyses of the results showed that as concentration increases, there was increase in the inhibitor while increase in temperature reduces the inhibition respectively. Moreover, the highest inhibition efficiency was 94.24 % at 40 oC and 0.25 g/l inhibition concentration in sulfuric acid medium while inhibition efficiency of 89 % at 60 oC and 0.20 g/l inhibition concentration in hydrochloric acid. The thermodynamic parameters revealed that the adsorption of extract onto the metal surface was spontaneous. Langmuir isotherm best fits the data obtained suggesting physical adsorption as the adsorption mechanism between the extract and the mild steel substrate. The results from the FT-IR spectroscopy showed that the organic compounds found in Rice husk made it a good inhibitor.